Impact of Mobile Technology Use on Knowledge Management in the Education Sector - Eka, Muhammad; Lubis, Yessi Fitri Annisah; Handoko, Divi; Rismayanti, Rismayanti; Supiyandi, Supiyandi (Raskha Media Group, 2025)
The integration of mobile technology into knowledge management (KM) practices has reshaped the landscape of information sharing and learning in the education sector. This study explores how mobile devices and applications contribute to the efficiency, accessibility, and effectiveness of KM processes among educators, students, and administrators. With the growing adoption of smartphones, tablets, and mobile learning platforms, educational institutions are experiencing a shift from traditional knowledge repositories to dynamic, real-time knowledge exchange environments. The research employs a mixed-method approach involving surveys and in-depth interviews with teachers, students, and IT staff across several secondary and higher education institutions. The findings reveal that mobile technology enhances knowledge acquisition and dissemination by enabling anytime-anywhere access to learning materials, collaborative tools, and institutional knowledge databases. However, challenges such as data security, digital literacy gaps, and resistance to change remain significant barriers to optimal utilization. Furthermore, the study highlights the role of institutional policies and support systems in facilitating effective mobile-based KM adoption. The results indicate that institutions with clear mobile technology strategies and investments in user training are more likely to achieve improved knowledge-sharing outcomes. This research provides practical insights into leveraging mobile technology to strengthen KM frameworks in education and emphasizes the need for continuous adaptation to technological advancements to sustain knowledge-based performance improvements.